Exploring problems for school reintegration following spinal cord injury: Perspectives on the kindergarten through fifth-grade population - Reeves, Brooke; Martin, Rebecca (Frontiers in Rehabilitation Sciences, 2022)
When a child acquires a spinal cord injury or disorder (SCI/D), they are faced with a sudden onset of changes. Engagement in education, play, and leisure are immediately impacted. Using survey methodology, return to school for children in grades kindergarten through fifth grade following SCI/D was examined. Families at a large spinal cord rehabilitation center for the pediatric population on the East Coast of the United States were surveyed via email about their child’s return to school, to understand supports and barriers a child faces when returning to school following SCI/D. Survey findings indicated that children face barriers upon return to school, related to school access, transportation, and educational support. The primary barrier identified was access to educational support. Using survey findings, an in-clinic outpatient return to school recommendation form was developed to bridge the gap between medical model therapists and school staff that is specific to each child’s needs. Curriculum is being developed to support families and therapists in preparing a child to return to school following SCI/D and to educate families to advocate for their child in the school setting. Future recommendations include further research regarding the placement of children in the school environment following SCI/D.